High serum bicarbonate and adverse outcomes in hemodialysis Patients - Ávila,Gonçalo (2021)
ABSTRACT Metabolic acidosis is a usual complication of progressive chronic kidney disease and is associated with morbidity and mortality. The correction of metabolic acidosis is a main goal of dialysis. In prevalent hemodialysis patients, acid-base homeostasis depends on many factors, mainly net acid production, amount of alkali given by the dialysate bath and duration of the interdialytic period. At present, the main concern in prevalent hemodialysis patients is not over patients with metabolic acidosis, but rather about the growing numbers of patients with metabolic alkalosis. Several large cohort studies have shown significant associations between high predialysis bicarbonate, as well as blood pH, and morbidity and mortality risk. Based on recent guidelines, we should keep predialysis serum bicarbonate concentrations at 24-26 mEq/L, although this is opinion-based and there is no consensus on the issue. Furthermore, there should be specific focus on the patient´s nutritional status and reversible comorbidities.